Bond strength durability of self-etching adhesives and resin cements to dentin (Journal of Applied Oral Science, 2009)
OBJECTIVES: To evaluate the microtensile bond strength (µTBS) of one- (Xeno III, Dentsply) and two-step (Tyrian-One Step Plus, Bisco) self-etching adhesive systems bonded to dentin and cemented to chemically cured (C&B Metabond) or light-cured paste of a dual-cure resin cement (Variolink II, Ivoclar) within a short (24 h) and long period of evaluation (90 days). MATERIAL AND METHODS: Forty recently extracted human molars had their roots removed and their occlusal dentin exposed and ground wet with 600-grit SiC paper. After application of one of the adhesives, the resin cement was applied to the bonded surface and a composite resin block was incrementally built up to a height of 5 mm (n=10). The restored teeth were stored in distilled water at 37ºC for 7 days. The teeth were then cut along two axes (x and y), producing beam-shaped specimens with 0.8 mm² cross-sectional area, which were subjected to µTBS testing at a crosshead speed of 0.05 mm/min and stressed to failure after 24 h or 90 days of storage in water. The µTBS data in MPa were subjected to three-way analysis of variance and Tukey's test (α= 0.05). RESULTS: The interaction effect for all three factors was statistically significant (three-way ANOVA, p